High hydrostatic pressure processing of beef patties: effects of pressure level and sodium tripolyphosphate and sodium chloride concentrations on thermal and aggregative properties of proteins - Speroni, Francisco (2014)
Beef patties added with sodium tripolyphosphate (STPP; 0, 0.25 or 0.5%) and/or NaCl (0, 1 or 2%) were treated at 200 or 300 MPa (5 min, 5 °C) or kept refrigerated (non-pressurized). In non-pressurized patties, NaCl-solubilized proteins were denatured, whereas STPP-solubilized proteins remained in native state. At 200 MPa, myosin head was more sensitive to high hydrostatic pressure (HHP) than actin. 1% NaCl favored HHP-induced denaturation of myosin head and actin, whereas 0.25% STPP protected against that effect. At 300 MPa, STPP favored HHP-induced denaturation of myosin head, actin and other proteins. The effect of STPP at 200 MPa may depend on the presence of specific binding sites for STPP anion, which would be destroyed at 300 MPa. Insoluble aggregates were formed at 300 MPa in samples without salts. Salts minimized protein aggregation was observed at 300 MPa. Noticeable differences in thermal and aggregative behavior occurred whether HHP level was 200 or 300 MPa. Industrial relevance: Currently, the reduction of sodium content in the manufacture of meat products is a hot topic and it is expected that this issue will become more relevant in the next years, as response to consumers' demands. Soluble high hydrostatic pressure-denatured beef proteins may provide interesting texture and technological properties to meat products with reduced salt content.